IRRIGATED MAIZE CROP: GRAIN YIELD IN TWO SOWING SEASONS IN THE MUNICIPALITY OF TERESINA, PIAUÍ - CARDOSO, MILTON JOSÉ; CARVALHO, HÉLIO WILSON LEMOS; ROCHA, LEONARDO MELO PEREIRA; GUIMARÃES, LAURO MOREIRA; GUIMARÃES, PAULO EVARISTO (International Journal of Maize & Sorghum, 2020)
The objective of this work was to evaluate commercial maize hybrids, under conventional sprinkler irrigation, in two sowing seasons (July and August 2017), in the municipality of Teresina, Piauí. A randomized block design was used, with two replications and 39 treatments (commercial maize hybrids). The characteristics evaluated were grain yield, water use efficiency, number of ears and number of grains per area. For the experiment with sowing done in July 2017, the average grain yield was 9.82 Mg ha-1 and the water use efficiency was 1.9 kg m-3, which are, respectively, 4.7 % and 15.8 % higher in relation to the experiment with sowing done in August 2017. Regardless of the sowing season, grain yields over 10.0 Mg ha-1 of three hybrids (LG 6418, CD 3880 PW and 2A 401 PW) stand out. The yield components, number of kernels per ear and grain mass per ear, show high values of correlation (over 0.80) with grain yield.